Analisis Perencanaan Pengelolaan Keuangan Desa Studi Kasus Desa Sidomulyo Kecamatann Bilah Hilir Kabupaten Labuhan Batu - tri mulyani, Nurlaila, laylan Syafina (Department of Islamic Accounting, Faculty of Islamic Economics and Business, IAIN Sultan Amai Gorontalo, 2023)
This study aims to analyze village financial management planning in Sidomulyo Village, Bilah Hilir District, Labuhan Batu Regency and to determine the compatibility between financial management planning in Sidomulyo village and PERMENDAGRI No.113 of 2014 concerning Village Financial Management Guidelines. This research is a descriptive qualitative research. The Head of Sidomulyo Village, Secretary of Sidomulyo Village, Treasurer of Sidomulyo Village, and BPD Sidomulyo are listed as subjects in this essay. In 2016. The three datasets being studied in this study are RPJMDesa, RKPDesa, and RAPBDesa. The data collection methods used in this study were observation, documentation, and interviews. The results of this study show that financial management planning in Sidomulyo village is now operating as it should, with the exception of one section in Permendagri No. 113 of 2014 which has not been implemented.